1986
DOI: 10.1063/1.527306
|View full text |Cite
|
Sign up to set email alerts
|

Classification of ten-dimensional kinematical groups with space isotropy

Abstract: All the abstract ten-dimensional real Lie algebras that contain as a subalgebra the algebra of the three-dimensional rotation group (generators J) and decompose under the rotation group into three three-vector representation spaces (J itself, K, and P) and a scalar (generator H) are classified. In all cases, the existence of a homogeneous space of dimension 4 is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 2 publications
2
103
0
Order By: Relevance
“…These are defined as the four-dimensional coset spaces exp(tH + q i P i ) of the Newton-Hooke groups, i.e as the quotients of N ± 10 by the subgroup SO(3) ⊗ L R 3 generated by the J i and the K i . This is analogous to defining Minskowski space as the coset E(3, 1)/SO(3, 1) ; in fact Bacry and Nuyts [15] have shown that all 10-dimensional kinematical groups have a four dimensional space-time interpretation.…”
Section: Newton-hooke Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are defined as the four-dimensional coset spaces exp(tH + q i P i ) of the Newton-Hooke groups, i.e as the quotients of N ± 10 by the subgroup SO(3) ⊗ L R 3 generated by the J i and the K i . This is analogous to defining Minskowski space as the coset E(3, 1)/SO(3, 1) ; in fact Bacry and Nuyts [15] have shown that all 10-dimensional kinematical groups have a four dimensional space-time interpretation.…”
Section: Newton-hooke Spacetimesmentioning
confidence: 99%
“…The two Newton-Hooke groups N ± 10 appear to have first surfaced in the work of Lévy-Leblond and Bacry [1] (see also [15]) who classified the possible ten-dimensional kinematic Lie algebras. The commutation relations of their Lie algebras n ± 10 are…”
Section: The Newton-hooke Groupsmentioning
confidence: 99%
“…Just as the Poincaré group contracts to the Galilei group or the Carroll group [1,2], the de-Sitter and Anti-de-Sitter groups have interesting contractions which have been classified in [3,4]. One may also obtain the Poincaré group as a contraction of the de-Sitter or Anti-de-Sitter groups and these are in fact the only groups for which this is possible [42].…”
Section: Kinematics Of Homogeneity and Isotropymentioning
confidence: 99%
“…The Carroll group, and the Galilei group are both kinematic groups of a spacetime in the sense of [39,40] and both may be regarded as the symmetry group of a structure in a Lorentzian spacetime with one higher dimensions.…”
Section: Resultsmentioning
confidence: 99%